Development Of K-Hayat Biodiversity Board Game Media To Improve Grade IV Learning Outcomes - Melyna Putri Viola; Barokah Isdaryanti (Inovasi Sekolah Dasar: Jurnal Kajian Pengembangan Pendidikan, 2026)
The lack of variety in the use of media in supporting social studies learning, only relying on package books and worksheets, so that from this grade IV students of SD Negeri 9 Purwodadi are less enthusiastic in learning social studies and quickly feel bored to the point of not understanding the material given by the teacher. Students who do not understand the learning material are shown by the learning outcomes of students in social studies subjects which are below average. The research aims to develop a viable and effective Biodiversity Board Game (K-HAYAT) media in improving student learning outcomes. The research uses the Reasearch and Development (R&D) research type Borg and Gall. The research subjects of SD Negeri 9 Purwodadi students amounted to 32 students. Data collection was obtained by test techniques and non-test techniques. The results of the feasibility assessment by expert validators obtained an average of 91.65% of the very feasible category. The results of the N-Gain test have a high category, with a small-scale score of 81.63% and a large-scale score of 76.05%. So that the K-Hayat Board Game media is declared feasible and effective in improving the learning outcomes of grade IV students in biodiversity materials.